ISLAM AND MULTICULTURAL THEOLOGY - Latif, Muhaemin (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This article discusses the relationship between Islam and multicultural theology. It employs qualitative research methodology with focusing on library research in getting documents relating to the issue. Islam and multicultural theology are two important disciplines that need to be reconsidered to capture the dimensions of similarities for both of them. Although multicultural theology is originally coined in the history of western countries like America and European countries and it is more likely concerned with Christian theology, it does not mean that Islam and multicultural theology have no relevant connection. The author comes to conclude that these issues are strongly related in the theoretical framework as well as in practical. Issues such as respect, recognition, and tolerance are crucially important for both of them. Islam itself makes those aspects the fundamental philosophy in social interaction, particularly, love and humanism are the key elements of Islam. The last mentioned are not seriously taken into account in multicultural theology which is a more formal or legal relationship.